Dual Output Power Management Unit for PV-Battery Hybrid Energy System - Rezk, Ahmed Ayman (AUC Knowledge Fountain, 2015)
The tremendous evolution in the electronics industry has provided high performance portable devices. However, the high power demand and the limited capacity of batteries, prevent the devices from operating for a long time without the need of a power outlet. The ease of deploying Photovoltaic (PV) cells close to the device enables the user to harvest energy on the go, and get rid of the conventional power outlets. However, applying the PV power to the electronic devices is not as easy as the plug and play model, due to the unstable output voltage and power of the PV cells. In this thesis, a power management unit is proposed to provide dual regulated outputs using a PV module and a rechargeable battery. The main components of the unit are a Dual Input Multiple Output (DIMO) DC-DC converter and a digital controller. The converter is used to interface the battery and the PV module with the loads. Moreover, the proposed converter has the ability to step up or step down the input voltage. The controller maximizes the PV power using the fractional open circuit voltage Maximum Power Point Tracking (MPPT) method. Furthermore, the controller manages the amount of power supplied to or from the battery in order to satisfy the load demand and regulate the outputs at the required levels. The controller has been implemented and synthesized using VHDL. A prototype has been implemented using an FPGA and off the shelf components. The functionality of the system has been tested and verified under varying environmental conditions.